Republic of Estonia : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This Selected Issues paper focuses on financing constraints and productivity in Estonia. The paper examines two questions: (1) is there evidence of financing constraints among Estonian firms; and (2) have financing constraints reduced firm-level total factor productivity (TFP)? These questions are particularly important in the current environment, in which credit growth in Estonia has slowed down considerably and firms may face increasing financing constraints that could dampen growth. The paper also provides empirical evidence on the existence of financing constraints among Estonian firms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet